Electricity transportation using HVDC technology for Algerian southern sun power plants - Nedjem Eddine Benchouia; Mohammed SAAIDIA; Abdelghani GUECHI (My University, 2023)
Algeria is worldly known as one of the big producers and exporters of fossil fuels. However, by developing an adequate energy policy, it could become one of the great sun power (SP) producers and exporters. Indeed with almost 2 million Km2 sunny superficies, the country detains enormous SP energetic potential funds. However, eventual powerful SP plants deployment could be done far to the southern Algerian desert which makes HVDC technology the best candidate for the transmission of produced electricity towards the north region where are the main industrial poles and the most populated regions for local consumption and eventually farther to the north for electricity exportation to the European countries. Theprospection work presented hereafter is a study on the feasibility of using HVDC technology for such possible projects according to country’s existingmeans and topographical and environmental characteristics.